A novel p–n Mn0.2Cd0.8S/NiWO4 heterojunction for highly efficient photocatalytic H2 production. Issue 35 (21st August 2020) - Feng, Haoqiang; Xi, Yue; Huang, Qunzeng
Abstract : A novel Mn0.2 Cd0.8 S/NiWO4 composite was fabricated and it exhibited enhanced H2 production activity due to the p–n heterojunction between Mn0.2 Cd0.8 S and NiWO4 . Abstract : Constructing a p–n heterojunction has been regarded as an effective way to restrain charge recombination and boost photocatalytic H2 production activity. Herein, a novel Mn0.2 Cd0.8 S/NiWO4 composite was fabricated by a hydrothermal process and which exhibited enhanced H2 production activity and excellent photostability. Particularly, the composite with 30 wt% of NiWO4 achieved the optimal H2 production rate of 17.76 mmol g −1 h −1, which was 2.9 times higher than that of Mn0.2 Cd0.8 S. The increased H2 production property was mainly due to the p–n heterojunction between Mn0.2 Cd0.8 S and NiWO4, which provided an efficient path for charge transfer and inhibited the photocorrosion of Mn0.2 Cd0.8 S. This work can offer technical support for the design and development of p–n heterojunctions that can be applied for photocatalytic H2 production.